Assessing narrative competence in preschool children: Key measures and ensuring reliability and validity - Wu, Bo; Jamal Rizal, Razali (NUN Gemilang ENT., 2025)
This study employed a content analysis approach to review the literature on the assessment of narrative competence in preschool children, focusing on evaluation dimensions, reliability, and validity. The findings reveal that narrative competence assessment primarily revolves around macrostructure and microstructure analyses. Macrostructure analysis emphasizes story grammar and plot coherence, while microstructure analysis examines lexical diversity, syntactic complexity, and productivity. Reliability is predominantly reported through inter-rater reliability metrics, with limited exploration of test-retest reliability or internal consistency. Validity evidence, such as convergent and discriminant validity, highlights the multidimensional nature of narrative competence and its close associations with skills like vocabulary and higher-order cognitive functions. This study underscores the importance of developing reliable and culturally inclusive tools for assessing narrative competence, providing a theoretical foundation for future research and practice in early childhood education.